2001
DOI: 10.1034/j.1600-0773.2001.d01-104.x
|View full text |Cite
|
Sign up to set email alerts
|

L-Cysteine and Sodium Hydrosulphide Inhibit Spontaneous Contractility in Isolated Pregnant Rat Uterine Strips in vitro

Abstract: The control of myometrial contractility during pregnancy and parturition is not fully understood. Gas signalling molecules, such as nitric oxide and carbon monoxide, have been shown to relax the myometrium and may be involved in the control of contractility. Hydrogen sulphide has recently been shown to be produced endogenously in animal and human tissue and to have a signalling function. The aim of the study was to investigate the effect of L-cysteine and sodium hydrosulphide, potential hydrogen sulphide donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…Notwithstanding these experimental conditions clear effects of GYY4137 are apparent. Consistent with previous work [6], [29] we found that NaHS decreased or even abolished spontaneous contractility in rat and human myometrium.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Notwithstanding these experimental conditions clear effects of GYY4137 are apparent. Consistent with previous work [6], [29] we found that NaHS decreased or even abolished spontaneous contractility in rat and human myometrium.…”
Section: Discussionsupporting
confidence: 93%
“…Hydrogen sulphide (H 2 S) is a gaseous signalling molecule that has been implicated in several physiological and pathophysiological processes from long term potentiation [1] and inflammation [2], to smooth muscle contractility [3], [4], [5], [6]. Two cytosolic enzymes, cystathionine β-synthase (CBS) and cystathionine γ-lyase (CSE) [7] act on the sulphur containing amino acids, cysteine and homo-cysteine, to produce H 2 S [8], [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sidhu et al[21] previously showed that L-cysteine causes decreases in amplitude and frequency of spontaneous contractions of pregnant rat uterine strips in vitro , however, they did not show which H 2 S synthetic enzyme is involved in the action of L-cysteine. The present study demonstrated that endogenous H 2 S has dual effects on the contractility of human myomentrium as showing that L-cysteine dose-dependently inhibited spontaneous contraction amplitude in the concentration range of 10 −7 –10 −2 mol/L, whereas it induced tonic contraction and increased the frequency of spontaneous contractions at high concentration (10 −3 mol/L).…”
Section: Discussionmentioning
confidence: 92%
“…In another hand, it has also been shown to enhance the vascular tension [19] and provoke tachykinin-mediated bronchoconstriction [20]. Sidhu et al [21] recently reported that H 2 S inhibits spontaneous contractility of rat uterine strip in vitro . To date, there are no studies examining the roles of endogenous-produced H 2 S in regulating the contractility of human uterine smooth muscle in particular, during pregnancy and labour.…”
Section: Introductionmentioning
confidence: 99%